Examining Factors Influencing Language Acquisition Success in Indonesian Multilingual Classrooms - Adeoye, Moses Adeleke; Prastikawati, Entika Fani; Curle, Samantha (Universitas Pendidikan Mandalika, 2025)
This study examines the predictors of language acquisition success in Indonesian multilingual classrooms through the lens of major language acquisition theories, particularly social interactionist and cognitive perspectives. A quantitative approach was adopted, employing secondary data analysis from standardised language assessments of 100 secondary school students. Multiple regression analysis was used to explore the predictive effects of key variables, including socioeconomic status, prior academic performance, motivation, prior language exposure, cognitive abilities, and classroom teaching methods. Findings reveal that motivation, prior exposure, cognitive abilities, and collaborative learning strategies are stronger predictors of language proficiency than socioeconomic background. Moreover, informal learning environments and community support significantly enhanced students’ language development, underscoring the value of social interactionist perspectives. These results challenge the prevailing assumption that socioeconomic status is the primary determinant of language success and instead emphasise context-specific and learner-driven factors. The study highlights practical implications for language educators and policymakers: designing integrated curricula that combine formal and informal learning opportunities, prioritising motivational and collaborative teaching strategies, and developing early predictive models to identify at-risk learners. By reframing the predictors of language success, this research provides actionable insights for advancing multilingual education policy and practice in Indonesia and beyond.